Pharmacokinetic Profile of Metformin and SGLT2 Inhibitors alone and in Combination: a Pharmacokinetic Study in Wistar Rats - Fachi, Mariana Millan; Dias, Bruna Carolina Lui; de Oliveria, Jonata Augusto [UNESP]; Peccinini, Rosângela Gonçalves [UNESP]; Pontarolo, Roberto; de Campos, Michel Leandro (Betasciencepress Publishing, 2023)
Objective: To achieve glycemic control, a combination of drugs is eventually necessary, especially the dual therapy of SGLT2 inhibitors with metformin. Despite the value of combination therapy, understanding the pharmacokinetic properties is critical. Therefore, this study aimed to conduct the combined and isolated administration of hypoglycemic drugs to understand their pharmacokinetic properties. Methodology: The study was performed by gavage in twenty-five rats that were divided into five groups: metformin alone (60 mg/ kg), canagliflozin alone 20 mg/kg, canagliflozin and metformin (20 mg/kg and 60 mg/kg, respectively), dapagliflozin alone 2 mg/kg, and dapagliflozin and metformin (2 mg/kg and 60 mg/kg, respectively). Blood samples were collected between 0.25 and 36 hours postdose and quantified by an HPLC-MS/MS method. Results: The metformin pharmacokinetics showed values lower than those from literature, but the most relevant result was a significant change in Cmax (3400 ng/mL), AUC (872.4 ng.min/L) and CL/F (72 mL/min/kg) in the metformin with dapagliflozin group compared to metformin alone Cmax (523 ng/mL), AUC (106.8 ng.min/L) and CL/F (752 mL/min/kg). For canagliflozin, the Cmax of 6116.7 ng/mL observed in our study was similar to that observed in literature, while the clearance (5.1 mL/min/kg) was higher than that of literature, which was 3.5 mL/min/kg. Clearance of dapagliflozin CL/F was reported as 3.33 mL/min/kg, while our result was 4.6 mL/ min/kg. The same study also published dapagliflozin half-life and MRT, which were slightly lower than our findings. In general, the parameters of canagliflozin and dapagliflozin were similar to the literature and did not change with simultaneous administration with metformin. Conclusion: Dapagliflozin significantly changed the pharmacokinetic disposition of metformin, while metformin coadministration had no influence on the pharmacokinetics of SGLT2 inhibitors.
Keywords: Pharmacokinetic of metformin; Rats; SGLT2 inhibitors